More Fun in the Philippines? Factors Affecting Transfer of Western Field Methods to One Developing World Context. - Andres, Juan Miguel L (Archīum Ateneo, 2015)
This paper presents some of the challenges encountered by a field research team when deploying an educational game for Physics. These included problems with site infrastructure and institutional support, logistical challenges, compliance with ethics requirements, launch delays, and student inattention or misunderstanding of directions. The paper shares these experiences with the wider community to help fellow researchers prepare, should they decide to conduct field studies in the Philippines.